Therapeutic potential of flavonoids from traditional Chinese medicine in pancreatic cancer treatment - Wan, Qi; Ren, Qing; Qiao, Shuangying; Lyu, Aiping; He, Xingwei; Li, Fangfei (Frontiers in Nutrition, 2024)
Pancreatic cancer (PC) is a highly aggressive malignancy with rising mortality rates globally. Its diagnosis is often challenging due to its asymptomatic nature in the early stages. Consequently, most patients receive a poor prognosis, with low survival rates within five years, as the disease is typically detected at an advanced stage, complicating effective treatment. Flavonoids, especially those derived from traditional Chinese herbal medicines, have attracted considerable attention for their potent anti-PC properties. This review highlights the therapeutic potential of these bioactive compounds, which modulate key biological pathways, making them promising candidates for PC intervention. Their mechanisms of action include the regulation of autophagy, apoptosis, cell growth, epithelial-mesenchymal transition, and oxidative stress, as well as enhancing chemotherapeutic sensitivity, exerting antiangiogenic effects, and potentially boosting immunomodulatory responses.The demonstrated benefits of these natural compounds in cancer management have spurred extensive academic interest. Beyond their role as anti-cancer agents, flavonoids may provide both preventive and therapeutic advantages for PC, resonating with the core principles of traditional Chinese medicine for disease prevention and holistic treatment.